Microalgae biodiesel: A review on oil extraction, fatty acid composition, properties and effect on engine performance and emissions - Deshmukh, Suchit; Kumar, Ritunesh; Bala, Kiran (Fuel processing technology, 2019)
Microalgae are explored as the sustainable source of biodiesel production considering their multi restorative effects on water and air. In spite of rapid growth and high lipid content, production of microalgal biodiesel is energy intensive and costly affair. Efficient oil extraction is one of the major hurdles; which needs special attention for making the microalgae biodiesel production process economical. Current review paper discusses various types of extraction methods starting from conventional organic solvent extraction method to advance methods like microwave irradiation, ultrasound, supercritical fluids and ionic liquids for oil extraction and also the direct transesterification. Modern methods give better yield in comparison to conventional methods. The variation of properties of microalgae biodiesel with respect to fatty acid methyl ester (FAME) composition is also highlighted and the properties are compared against established standards. Also, the previous studies on performance and emission characteristics using microalgae have been reviewed and it is found that microalgae biodiesel is on comparable scale to that of first and second generation biofuel. Lots of research scope and further developments in harvesting, drying, oil extraction and direct transesterification stages can potentially establish microalgae as next generation source for transport fuel production. •A comprehensive review of lipids in microalgae cells and their fatty acid composition•Review of novel oil extraction ways: ultrasound, microwave and supercritical fluid•Review of direct transesterification methods•Analysis of microalgae biodiesel properties and effect on diesel engine